Analysis of Corruption Justice In The Perspective of Legal Sociology - Kayla Zendy Alfanny Hayfa; Christine S.T. Kansil (Publikasi Indonesia, 2023)
Sociology is ethical behavior. It is known that it is usually distinguished between mere behavior and ethical behavior (which is based on a clear conscience). His behavior includes behavior in the areas of trust, decency, disobedience, and law. Behavior that can be distinguished between normal behavior (fixed) and unique behavior Sociology of law pays attention to its attention to the law as a social phenomenon (behavior) with its reciprocal influence on other social phenomena (behavior too). Thus the possibility that one party is considered as an influencing factor (independent variable) and the other party is considered as an influencing factor (independent variable). Careful research activities are required. However, the sociology of law does not prioritize because both are the center of attention of science. Thus, the sociology of law first focuses on unwritten or customary law, usually customary law. With the first criterion, the behavior of carrying out the law (as), from other symptoms.